2020
DOI: 10.17743/jaes.2020.0004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Head-Related Transfer Function Individualization on Task Performance: Case of a Virtual Reality Shooter Game

Abstract: This paper presents the results of an extended experiment to assess the impact of individualized binaural rendering on player performance in an ecologically valid use context, specifically that of a VR "shooter game," as part of a larger project to characterize the impact of binaural rendering quality in various VR type applications. Participants played a simple game in which they were faced with successive targets approaching from random directions on a sphere. While audiovisual cues allowed for general targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In addition, it was characterised by the presence of goal-directed actions toward each sound. We built on works in which interactions with sound sources occurred using reaching movements, as in some pioneers VR approaches [ 21 , 22 ] and more recent studies [ 23 ]. A motor approach based on hand movements in the space of the sound sources has also been adopted by Valzolgher and colleagues [ 13 ], in a study that demonstrated the effect of kinesthetic cues when re-learning to localize sounds with one ear plugged, as here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was characterised by the presence of goal-directed actions toward each sound. We built on works in which interactions with sound sources occurred using reaching movements, as in some pioneers VR approaches [ 21 , 22 ] and more recent studies [ 23 ]. A motor approach based on hand movements in the space of the sound sources has also been adopted by Valzolgher and colleagues [ 13 ], in a study that demonstrated the effect of kinesthetic cues when re-learning to localize sounds with one ear plugged, as here.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adapting to new auditory cues may be easier through motor interactions with the sound sources, using tasks in which acoustic stimulation results from the subjects’ own movements [ 13 ] or in which participants are encouraged to act towards sounds [ 19 , 20 ]. For instance, participants could be asked to hit a moving sound presented in a virtual auditory space using a hand-held tool [ 21 , 22 ], or to shoot audio-visual moving targets in virtual reality [ 23 ]. Other relevant examples include the work of Steadman and colleagues, in which participants were required to actively point their head toward sounds [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The premise of the present study is that HRTF selection can be reduced to its essential: that given the variance on bestmatch selection [17,18], and its limited impact on immediate localization performance [6,18], it is preferable to capitalize on training to improve localization accuracy. Still, previous studies have shown that using perceptually poorly-rated HRTFs led to a significant increase in adaptation time compared to best-rated ones [6,19].…”
Section: Previous Work 21 Hrtf Selection Methodsmentioning
confidence: 99%
“…Combining the desire for robust evaluation techniques with realistic use cases requires a delicate balance of experimental design in order to present a real-world like context while still maintaining the required laboratory controllability in order to obtain meaningful exploitable data (e.g. [12]).…”
Section: Immersionmentioning
confidence: 99%